2015
DOI: 10.11005/jbm.2015.22.2.51
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Osteogenic Activity of Suberoylanilide Hydroxamic Acid is Synergized by BMP-2

Abstract: BackgroundMany histone deacetylase (HDAC) inhibitors are well recognized as potential anti-cancer drugs. Inhibition of HDACs induces temporal transcription or epigenetic control, thus regulating many different biological responses. Here, we investigated the osteogenic effect of the HDAC inhibitor suberoylanilide hydroxamic acid (SAHA; vorinostat).MethodsThe effects of SAHA on osteoblast differentiation were examined in the 6XOSE-Luc reporter assay for determination of runt-related transcription factor 2 (Runx2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“… 191 HDAC inhibitor suberoylanilide hydroxamic acid (SAHA; vorinostat) increases the Runx2 promoter acetylation to intrigue Runx2 expression and osteoblastogenesis, in a BMP2- dependent manner. 192 The Bmp2 promoter regions of the genes are epigenetically locked with increased CpG methylation and decreased H3K9 acetylation. 193 And CpG-demethylating agent or the HDAC inhibitor trichostatin-A renders Bmp2 expression.…”
Section: Regulation Of Bmp and Tgf-β Signaling In Bonementioning
confidence: 99%
“… 191 HDAC inhibitor suberoylanilide hydroxamic acid (SAHA; vorinostat) increases the Runx2 promoter acetylation to intrigue Runx2 expression and osteoblastogenesis, in a BMP2- dependent manner. 192 The Bmp2 promoter regions of the genes are epigenetically locked with increased CpG methylation and decreased H3K9 acetylation. 193 And CpG-demethylating agent or the HDAC inhibitor trichostatin-A renders Bmp2 expression.…”
Section: Regulation Of Bmp and Tgf-β Signaling In Bonementioning
confidence: 99%
“…In this manner, a strategy for increasing the level of RUNX2 protein acetylation is a unique alternative to compensating for a reduced RUNX2 level. Many HDIs, such as SAHA 52 , TSA 53 , valproic acid 54 , sodium butyrate 55 , and MS-275 56 , have been indicated as therapeutics for osteopenic conditions. Among these HDIs, MS-275 has shown strong osteogenic effects in cell culture and animal studies 56 .…”
Section: Treatment Of Ccd By Inhibition Of Runx2 Deacetylationmentioning
confidence: 99%
“…In a study, the treatment of C57BL/6J mice with SAHA caused decreased mineralization and OPN, COL1A1, and OCN gene expression, and eventually led to bone loss in rodents [ 120 ]. In contrast, other researches showed that optimum dose of SAHA had no negative effects on bone formation and could promote osteogenesis via upregulation of Runx2 and BMP-2-dependent ALP activity in both human bone marrow MSCs and an osteoporotic mice model [ 121 , 122 ]. These contradicting results for SAHA in osteogenesis indicate that it has a dose-dependent function during osteo-differentiation.…”
Section: Epigenetic Modifiers Known As Epidrugsmentioning
confidence: 99%